Correction: CO2 free production of ethylene oxide via liquid phase epoxidation of ethylene using niobium oxide incorporated mesoporous silica material as the catalyst. Issue 8 (9th February 2023) - Maqbool, Muhammad; Akhter, Toheed; Faheem, Muhammad; Nadeem, Sohail; Park, Chan Ho
Abstract : Correction for 'CO2 free production of ethylene oxide via liquid phase epoxidation of ethylene using niobium oxide incorporated mesoporous silica material as the catalyst' by Muhammad Maqbool et al., RSC Adv., 2023, 13, 1779–1786, ; https://doi.org/10.1039/D2RA07240H